Maternal and fetal serum levels of caspase-cleaved fragments of cytokeratin-18 in intrahepatic cholestasis of pregnancy. (16th February 2016) - Ersoy, Ali Ozgur; Kirbas, Ayse; Ozler, Sibel; Ersoy, Ebru; Ozgu-Erdinc, A. Seval; Ergin, Merve; Erkaya, Salim; Uygur, Dilek; Danisman, Nuri
Abstract: Objective : We aimed to investigate the relationship between intrahepatic cholestasis of pregnancy (ICP) and caspase-cleaved fragments of cytokeratin-18, also referred to as M30, a marker of apoptosis. Methods : In this case–control study, maternal and umbilical cord blood venous samples were obtained from 21 pregnant women with ICP and 22 healthy pregnant women as a control group. M30 levels were compared among the groups. Results : Maternal serum M30 levels were significantly higher in the severe ICP group than in the control ( p  < 0.001) and mild ICP groups ( p  = 0.006). The values were comparable between the mild ICP and the control groups. The umbilical cord serum M30 levels were also significantly greater in the severe ICP group than in the control group ( p  = 0.001). Conclusions : Changes in M30 levels, as an apoptosis marker, may shed light on the pathogenesis of ICP. Explaining the mechanisms of bile acid (BA)-induced hepatocyte injury may contribute further therapeutic strategies for the treatment of human cholestatic diseases.